Child-care attendance and common morbidity: evidence of association in the literature and questions of design - Aluísio J. D. Barros
Papers on child-care attendance as a risk factor for acute respiratory infections and diarrhea were reviewed. There was great variety among the studies with regard to the design, definition of exposure and definition of outcomes. All the traditional epidemiological study designs have been used. The studies varied in terms of how child-care attendance in general was defined, and for different settings. These definitions differed especially in relation to the minimum time of attendance required. The outcomes were also defined and measured in several different ways. The analyses performed were not always appropriate, leading to sets of results of uneven quality, and composed of different measures of association relating different exposures and outcomes, that made summarizing difficult. Despite that, the results reported were remarkably consistent. Only two of the papers reviewed failed to show some association between child-care attendance and increased acute respiratory infections, or diarrhea. On the other hand, the magnitude of the associations reported varied widely, especially for lower respiratory infections. Taken together, the studies so far published provide evidence that children attending child-care centers, especially those under three years of age, are at a higher risk of upper respiratory infections, lower respiratory infections, and diarrhea. The studies were not consistent, however, in relation to attendance at child-care homes. Children in such settings were sometimes similar to those in child-care centers, sometimes similar to those cared for at home, and sometimes presented an intermediate risk.